Polycyclic aromatic hydrocarbons and other selected organic compounds in ambient air of Campo Grande City, Brazil - Re-Poppi, N.; Santiago-Silva, M. (Elsevier B.V., 2005)
Fourteen samples of particulate matter and semi-volatile organic compounds were collected during 6 months in the city of Campo Grande, South Mato Grosso State, Brazil. Particle-bound polycyclic aromatic hydrocarbons (PAHs) were collected on Fluoropore PTFE filters and gas-phase PAHs were collected into sorbent tubes with XAD-2 resin. Both types of samples were extracted with a dichloromethane/methanol mixture (4:1 v/v), then the extracts were subjected to gas chromatography-mass spectrometry (GC-MS) analysis. PAHs, oxidized PAH (oxy-PAHs), phenols and methoxyphenols were identified by use of GC retention indices and MS files. The average value obtained for the sum of 15 PAHs was 21.05 ng m(-3) (range: 8.94-62.5 ng m(-3)). The presence of specific tracers and calculations of characteristic ratios (e.g. [Phe]/[Phe] + [Ant]) were used to identify the sources of the emissions of PAHs in the atmospheric samples. Levoglucosan (the anhydride of beta-glucose), retene (1-methyl-7-isopropylphenanthrene) and methoxyphenols (derivatives of syringol and guaiacol) and tracers for wood burning were identified. This study demonstrates that biomass burning from the rural zone is the main source of PAHs and emissions of other substances in the investigated site of Campo Grande. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: BAH; Oxy-BAH; retention indices; Campo Grande City